Optimizing The Role of Parents in Early Literacy Development Early Childhood in The Digital Era: A Theoretical Study: Penelitian - Arnan Pahmi Matondang; Taupik Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Early literacy is a crucial foundation for children's thinking development during their golden years. In today's digital skills in children, particularly in today's digital age. Using a literature review approach, this article discusses what early literacy actually is, the role of parents in it, the impact of digital media on children's learning, and the age, parents' role as primary educators is increasingly crucial in helping children develop early reading and writing skills, particularly within the home. This scientific article explores how parents can optimally engage in fostering early literacy challenges and opportunities that arise from digitalization. The study found that parental involvement can be enhanced through simple yet effective methods, such as encouraging children to read at home, fostering collaborative communication between parents and children, and intelligently and wisely digital media as a tool to stimulate early literacy skills.